2017
DOI: 10.1186/s12969-017-0167-z
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile idiopathic arthritis in relation to perinatal and maternal characteristics: a case control study

Abstract: BackgroundExisting data on associations between maternal and early childhood exposures and juvenile idiopathic arthritis (JIA) risk is scant and inconsistent with previous studies showing potential role for prematurity, number of siblings and infections. We explored JIA and International League of Associations for Rheumatology (ILAR) JIA categories in relation to selected infant (birthweight, size-for-gestational-age, gestational age), and maternal (parity, delivery type, prior fetal loss) characteristics that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 21 publications
3
31
0
Order By: Relevance
“…The findings of this study were supported by a Swedish study of 3334 JIA cases compared to 13,336 of controls, which likewise reported higher rates of being born by CS among children with JIA compared to controls (OR 1.1, 95% CI 1.0 to 1.3). Finally, a Northern American study of 1234 subjects with JIA and 5,993 controls found a modest, non‐statistically significant increased risk of JIA associated with CS . Both the Swedish and Northern American studies failed to take into account whether or not the CS was elective.…”
Section: Early Life Events and Jia Riskmentioning
confidence: 99%
See 3 more Smart Citations
“…The findings of this study were supported by a Swedish study of 3334 JIA cases compared to 13,336 of controls, which likewise reported higher rates of being born by CS among children with JIA compared to controls (OR 1.1, 95% CI 1.0 to 1.3). Finally, a Northern American study of 1234 subjects with JIA and 5,993 controls found a modest, non‐statistically significant increased risk of JIA associated with CS . Both the Swedish and Northern American studies failed to take into account whether or not the CS was elective.…”
Section: Early Life Events and Jia Riskmentioning
confidence: 99%
“…Three registry studies have investigated the association between mode of delivery and future risk of JIA. In a large Danish epidemiological study of 1380 children with JIA and 789 189 controls, after adjustment for multiple potential confounding factors (gestational age, sex, birth weight, maternal age, maternal smoking during pregnancy, and complications during pregnancy), children delivered by cesarean section (CS) had an increased risk of JIA, with a hazard ratio of 1.25 (95% CI 1.04 − 1.51) compared to controls.…”
Section: Early Life Events and Jia Riskmentioning
confidence: 99%
See 2 more Smart Citations
“…It is one of the most common chronic diseases of childhood, with the annual incidence and prevalence rates ranging from 1.6 to 23 per 100,000 and 3.8 to 400 per 100,000, respectively (2). The exact etiology of JIA is unclear; however, both genetic and environmental factors are thought to play a role in the pathophysiology of the disease (3).…”
Section: Introductionmentioning
confidence: 99%